2021
DOI: 10.1177/17411432211034167
|View full text |Cite
|
Sign up to set email alerts
|

Learning–centred leadership and student achievement: Understanding the mediating effect of the teacher professional community and parental involvement

Abstract: This paper examines the links between learning–centred leadership and student achievement through the mediating effect of teacher professional community and parental involvement. Using teacher and student survey data collected from 79 lower secondary Turkish schools in 12 provinces across the country in 2019, this study employs multilevel structural equation modelling. The findings of the current study add to the growing knowledge base in the non-western societies, revealing the impact of principals’ leadershi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 74 publications
(121 reference statements)
2
8
0
Order By: Relevance
“…Unlike previous studies that examined the relationship between principal leadership and PLCs from teachers' perspective, this study adopted principals' perspective to explore the effect of transformational leadership on PLCs. Results provide empirical evidence on the crucial role of transformational leadership in PLCs in China [29], and lend credence to findings of studies from teachers' perspectives that leadership matters a lot to the practice of PLCs [17,18,[21][22][23].…”
Section: Effect Of Transformational Leadership On Plc Componentssupporting
confidence: 60%
See 1 more Smart Citation
“…Unlike previous studies that examined the relationship between principal leadership and PLCs from teachers' perspective, this study adopted principals' perspective to explore the effect of transformational leadership on PLCs. Results provide empirical evidence on the crucial role of transformational leadership in PLCs in China [29], and lend credence to findings of studies from teachers' perspectives that leadership matters a lot to the practice of PLCs [17,18,[21][22][23].…”
Section: Effect Of Transformational Leadership On Plc Componentssupporting
confidence: 60%
“…Furthermore, research devoted considerable attention on how to establish effective PLCs. Various stages for the development of PLCs were identified [16], and the crucial role of principal leadership in implementing PLCs and promoting professional development is consistently highlighted [17][18][19]. In addition, studies have explored the effects of PLCs on teachers and students.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, as a result of descriptive analysis, it was understood that teacher perceptions of learning-centered leadership and teachers' professional learning were at medium-high level. While these averages for learning-centered leadership are similar to some studies conducted in Türkiye (Ertürk, 2022;Kılınç et al, 2020;Özdemir et al, 2021), it is seen that higher averages have been reached in some other studies (Bellibaş & Gümüş, 2021). Some studies conducted abroad have averages close to this current study (Alazmi & Hammad, 2021;Hammad et al, 2021;Kulophas & Hallinger, 2020, there are also some other studies with higher averages (Al-Mahdy et al, 2021;Alfayez et al, 2021;Hallinger & Liu, 2016;Hallinger et al, 2017Hallinger et al, , 2019Liu et al, 2016b;Talebizadeh et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, potential possible outcomes such as student learning and school improvement can be achieved together with the teachers' professional development (Al-Mahdy et al, 2021). Studies correlating learning-centered leadership with student achievement also support this finding (Özdemir et al, 2021;Reardon, 2011). Moreover, some other studies in the literature indicated that LCL has no direct effect on TPL and that the variables such as teacher trust and teacher agency mediated this relationship (Alazmi & Hammad, 2021;Bellibaş et al, 2020;Hallinger et al, 2017Hallinger et al, , 2019Tayag & Ayuyao, 2020).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation